Margens limiares da prosa contemporânea : a poética do fragmento em Eles Eram Muitos Cavalos, de Luiz Ruffato, e Ó, de Nuno Ramos - Coutinho, Ilmara Valois Bacelar Figueiredo (2014)
This thesis investigates the constant fragment of contemporary prose, having as empirical universe, the literary works They were many horses (Eles eram muitos cavalos) by Luiz Ruffato (2013) and Ó by Nuno Ramos (2008). In the seam of the undisciplined rooting that goes amalgamating themes, speeches, points of view, languages, space-times, among other territorialities put in dispersion, the poetic of fragment is built up through the intemperatedness of "eternal return" (Nietzsche, 1999 ), which expressiveness discusses the shattered, self-reflexive and multireferenced condition of the contemporaneity. It is a literature of multi-referential nature, theoretically founded by Agamben (2013), Barthes (2003, 2004, 2007a, 2007b, 2009), Bauman (1998, 2005), Benjamin (1987, 1994, 2000, 2009), Blanchot (2005, 2010a, 2010b, 2011), Canclini (2008), Dalcastagnè (2012), Deleuze & Guattari (1977, 1995), Deleuze (1990), Derrida (2001, 2005), Dias (2011), Foucault (2000, 2007, 2011), Hall (2003), Meffesoli (2007), Mosé (2005), Nietzsche (1999), Schollhammer (2011), Steiner (2012), Vaihinger (2011), among other authors. During the study, it was possible to deepen the perception that the order of the fragment, in the literary works studied here, is the order of roaming as much the writing will shape up lacunar, nomadic, unpredictable, as the propensity to apply for readings based on the clash of the (im) possibilities concerning the construction of the senses. The results indicate a prose geared to disallow exclusivist territorialities to differentiated spheres of knowledge, questioning the power of language by exposing ruins-powers that can multiply in the silent intervals that constitute them. The poetic of fragment is a literature of thresholds margins, requesting reader crossroad grip as well as drawing a pessimistic critique of capitalist societies, whose values of spectacle bear the misery of social existence and the trivialization of life.